Ambient carbon monoxide associated with alleviated respiratory inflammation in healthy young adults. (January 2016) - Zhao, Zhuohui; Chen, Renjie; Lin, Zhijing; Cai, Jing; Yang, Yingying; Yang, Dandan; Norback, Dan; Kan, Haidong
Abstract: There is increasing controversy on whether acute exposure to ambient carbon monoxide (CO) is hazardous on respiratory health. We therefore performed a longitudinal panel study to evaluate the acute effects of ambient CO on fractional exhaled nitric oxide (FeNO), a well-established biomarker of airway inflammation. We completed 4–6 rounds of health examinations among 75 healthy young adults during April to June in 2013 in Shanghai, China. We applied the linear mixed-effect model to investigate the short-term associations between CO and FeNO. CO exposure during 2–72 h preceding health tests was significantly associated with decreased FeNO levels. For example, an interquartile range increase (0.3 mg/m 3 ) of 2-h CO exposure corresponded to 10.6% decrease in FeNO. This association remained when controlling for the concomitant exposure to co-pollutants. This study provided support that short-term exposure to ambient CO might be related with reduced levels of FeNO, a biomarker of lower airway inflammation. Highlights: We completed 4–6 rounds of health examinations among 75 healthy young adults. Short-term CO exposure was significantly associated with decreased FeNO levels. The inverse association between CO and FeNO was robust controlling for co-pollutants. Abstract : Short-term exposure to ambient carbon monoxide may alleviate the respiratory inflammation.